The Influence of Internet Language on Improving Students’ Writing Skills Case Study of the Second Year EFL Students at the Department of English - University of Laghouat - Touissat, Meroua; Belhadj ,Abed Elkrim (Faculty of Letters and Foreign Languages Department of English, 2017)
The present study investigates the Influence of the Internet Language on improving students ‘writing skills. Online social networks have recently been perceived by educators and language specialists as an alternative method for EFL teaching and learning. This research investigates the perceptions and attitudes of second year students at Laghouat University towards the use of Internet Language learning writing. It also seeks to investigate the role that Internet Applications play in enhancing the writing performance level. A survey consisted of eleven questions was held to verify whether the students could benefit and take advantage of the Internet use to better their writing out comes. The concerned population involved students of the English department at Laghouat University enrolled in the second year 2016/2017. The obtained results supported our hypothesis that claim that the use of the Internet can contribute in improving the students’ writing out comes. Henceforth, we recommend the generalization of this new technology in our schools and universities to allow students take a maximum advantage of it